A New Member State in the EU Internal Security System – The Polish Perspective - Menkes, Jerzy (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The aim of the study is to reconstruct Poland's perception of the EU internal security system because this perception sets the framework for her participation in cooperation. The starting point of the analysis is a critical evaluation of methods and tools for presenting the non-economic goals of European integration in the acts constituting the institutionalization of cooperation. Criticism is based on the recognition that the way goals are set, applied in the practice of European integration, significantly impedes their internalization to a new member, whereas in accordance with the rules of policy-oriented jurisprudence, the awareness within the community of interests of the state determines the effectiveness of the law. The study of the institutionalization of cooperation is conducted in the interdisciplinary regime (international law and international relations) which facilitates learning about the state's conduct.The conclusions go beyond the Polish perspective; they constitute a generalization of the analysis of norms and facts.The deepening of the European integration in the field of home affairs may be regarded from two perspectives. The first assesses the methods of its implementation, i.e. the degree of observing the rule of law and the principles of democracy. From this perspective, integration may be – at best – seen as a praetor legem activity. In the second, integration may be perceived through the prism of the results achieved. From this perspective, a significant and tangible progress of integration may be noted, which allows an increase in the efficiency of expenditure and activity without duplicating efforts and structures.
Keywords: bezpieczeństwo wewnętrzne; integracja; system bezpieczeństwa wewnętrznego UE; państwo członkowskie; Unia Europejska; Polska